Employee Well-Being Research Trends in HR Management - Judijanto, Loso; Soesanto , Dasa Rahardjo; Pahrijal, Rival (West Science Interdisciplinary Studies, 2025)
Employee well-being has emerged as a critical focus within human resource management (HRM) research, driven by its direct impact on productivity, job satisfaction, and organizational success. This study explores recent research trends in employee well-being using a systematic literature review based exclusively on Scopus-indexed publications. The findings reveal that key themes in HRM well-being research include work-life balance, job satisfaction, burnout, leadership, digitalization, and corporate social responsibility (CSR). The bibliometric analysis highlights the increasing role of psychological well-being, mental health support, and diversity, equity, and inclusion (DEI) initiatives in shaping modern HRM strategies. Additionally, the growing integration of artificial intelligence (AI) and technology in well-being management presents both opportunities and challenges for organizations. The discussion underscores the practical implications of well-being research for HRM practices, emphasizing the need for leadership training, personalized employee support programs, and ethical technology use. The study also identifies future research directions, including the long-term effects of remote work, AI-driven HR analytics, and cross-cultural perspectives on well-being interventions. By synthesizing existing literature, this research provides valuable insights for HR professionals, policymakers, and academics seeking to enhance employee well-being in dynamic work environments.
Keywords: Employee Well-Being; Human Resource Management; Job Satisfaction; Work-Life Balance; Bibliometric Analysis